Production and potential application of pyroligneous acids from rubberwood and oil palm trunk as wood preservatives through vacuum-pressure impregnation treatment - Lee, Chuan Li; Chin, Kit Ling; Khoo, Pui San; Hafizuddin, Mohd Sahfani; H’ng, Paik San (MDPI, 2022)
The development of low-environmental-impact technologies for the elimination of biological damage is one of the vital goals of the wood protection industry. The possibility of utilizing pyroligneous acid as a wood preservative can be a great solution to extend the application of the currently fast-growing timber species, which has lower natural durability against biological damage. In this study, the effectiveness of pyroligneous acid as a wood preservative was evaluated by impregnating rubberwood with pyroligneous acid using vacuum-pressure treatment, and the treated woods were exposed to mould fungi, wood-decay fungi and termite attacks under laboratory conditions. Pyroligneous acids produced from rubberwood (RWPA) and oil palm trunk (OPTPA) at different pyrolysis temperatures were evaluated. To fully understand the effectiveness of pyroligneous acids as wood preservatives, different concentrations of pyroligneous acids were impregnated into rubberwood. Concentrations of 50% RWPA and 30% OPTPA were sufficient against mould and decay fungi on rubberwood. Rubberwood impregnated with pyroligneous acid acted as a slow-acting toxic bait to cause a high termite mortality rate due to toxic feeding and does not serve as a good repellent to prevent termites from feeding on the wood. In general, OPTPA has better biological durability compared to RWPA.